Caregiving tasks among adult siblings for elderly parents determinants and processes - De los Santos, Katrina Anna F.; Baviera, Sara Camille V.; Roldan, Aurorita T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study was an attempt to identify the types of caregiving or support adult siblings provide for elderly parents; to determine the conditions/factors that lead to or inhibit siblings to assume or fulfill caregiving tasks; and to determine the processes of the acquisition of caregiving tasks. The study is descriptive and qualitative in nature and used the Family Development and Exchange theory frameworks to guide the discussion and analysis of the data. Random sampling was used to select the participants. Surveys were given to one hundred and twenty employees from the University of the Philippines Diliman. Thirty participants who have siblings and provide caregiving or support to their elderly parent/s were selected. The main tool used for the study is an interview. To analyze the data gathered, frequency counts, percentages, and content analysis were used. Five types of caregiving or support emerged: financial support, co-residence, emotional support, service, and material things. Financial support was the most common type of support adult siblings provide for elderly parents. The majority views that fulfilling caregiving tasks for elderly parents is part of the Filipino culture and tradition. It was also found in the study that the most common factor considered by adult siblings in the acquisition of caregiving tasks is income with marital status and availability coming close. There are two processes in the acquisition of caregiving tasks found in the study. The process of deliberation uses intentional or incidental verbal communication to distribute the caregiving tasks among the adult siblings. The process of non-deliberation relies on the regularity of adult siblings in volunteering to accomplish tasks and on the willingness of each adult sibling. Non-deliberation was found to be the more popular process of acquiring caregiving tasks among siblings than deliberation.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Aging parents -- Home care -- Philippines; Aging parents -- Philippines -- Family relationships